Pengaruh Pijat Bayi Terhadap Peningkatan Berat Badan Bayi di Wilayah Kerja Puskesmas Gogagoman - Strahmwati Hamzah (Universitas Widya Nusantara, 2025)
According to the 2022 SSGI report, the prevalence of underweight and severely underweight toddlers was 17.1%. The 2023 SKI report in North Sulawesi showed that toddlers were wasting at 6.4% and severely wasting at 2.4%. Based on age, the number of infants (0-11 months) wasting was 9.5% and severely wasting at 3.9%. Infant massage is also an alternative effort to achieve the simplest level of health that can be done at home, but many mothers are afraid to massage their babies. The purpose of this study was to determine the effect of baby massage on infant weight gain. This study used a pre-experimental design with a one-group pretest-posttest design. This study was conducted in the Gogagoman Community Health Center. The sample size was 20 infants (3-11 months). The sampling technique used was total sampling. The results of the study showed that the average weight of babies before massage was 4.15 kg with SD 0.72 and the average weight of babies after massage was 5.86 kg with SD 0.76. The results of the statistical test obtained a value of p = 0.001 (p <0.05) meaning that there is an effect of baby massage on increasing infant weight in the work area of Gogagoman Community Health Center. The conclusion is that there is a difference in the average score (mean) of baby weight before and after being given a massage with a score of 1.71, meaning that baby massage can increase baby weight.